2019
DOI: 10.1016/j.ijme.2019.100319
|View full text |Cite
|
Sign up to set email alerts
|

Capability approach for realising the Sustainable Development Goals through Responsible Management Education: The case of UK business school academics

Abstract: This paper assesses whether RME can help UK business schools that are signatories to the PRME contribute to the realisation of any of the 17 SDGs through the lens of 15 UK business school academics. We found that RME (in the context of this study) can help business schools contribute directly to SDG4 and indirectly to the other goals, except for SDG3. The latter got little or no attention in this study, even though it appears that some business schools claim to be contributing to the realisation of this goal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
1
21
0
2
Order By: Relevance
“…Trends evident from the 2019 PwC SDG Challenge survey are consistent with several other surveys published over the past few years, all indicating growing use of the SDGs in driving business strategy for purposeful businesses (The British Academy, 2019). These trends are also apparent to us as educators in the number of schools and universities we have observed using the SDGs as a framework for advancing their social contributions and educational programmes (see, for example: Kemmy Business School, 2018; Ndubuka & Rey-Marmonier, 2019;Purcell et al, 2019). This, we believe, helps develop students' sustainability literacy which should help them contribute to pro-sustainability strategies as their careers progress into senior executive roles in the private, public and third sectorsresulting in what O'Dwyer and Unerman (Forthcoming) refer to as positive cohort effects in sustainability leadership.…”
Section: Contrasting Sdg Accounting Scholarship With Sdg Accounting Pmentioning
confidence: 84%
“…Trends evident from the 2019 PwC SDG Challenge survey are consistent with several other surveys published over the past few years, all indicating growing use of the SDGs in driving business strategy for purposeful businesses (The British Academy, 2019). These trends are also apparent to us as educators in the number of schools and universities we have observed using the SDGs as a framework for advancing their social contributions and educational programmes (see, for example: Kemmy Business School, 2018; Ndubuka & Rey-Marmonier, 2019;Purcell et al, 2019). This, we believe, helps develop students' sustainability literacy which should help them contribute to pro-sustainability strategies as their careers progress into senior executive roles in the private, public and third sectorsresulting in what O'Dwyer and Unerman (Forthcoming) refer to as positive cohort effects in sustainability leadership.…”
Section: Contrasting Sdg Accounting Scholarship With Sdg Accounting Pmentioning
confidence: 84%
“…Achieving this Goal, of the SDGs ensure successful outcomes for today's children by building the foundations for our societies' future wellbeing [3]. Healthy and educated children are better able to fulfil their potential and contribute to society [18].…”
Section: Conceptualization Of Children's Well-being and Methods Usedmentioning
confidence: 99%
“…Pizzi, Caputo, Corvino, and Venturelli (2020) analysed 266 articles between 2012 and 2019 finding four key themes of research appearing: technological innovation; firms' contribution in developing countries; non-financial reporting; and education for SDGs. Other authors have focused on the role of management education in supporting the achievement of the SDGs: Weybrecht (2017) spoke of the importance of management education working hand-in-hand with the business sector, whereas Ndubuka and Rey-Marmonier (2019) discussed capability approaches for management education to assist in achieving the SDGs in UK business schools. However, as Pizzi et al (2020) concluded, despite the rapidly increasing number of papers appearing, the contribution of business and management academics to the achievement of the SDGs remains very fragmented.…”
Section: University and Academic Initiatives Concerning The Sdgsmentioning
confidence: 99%